Fibroepithelial polyp in a female right breast nipple-Case Report - Hameed , Oula Fouad; Maktoof , Zainab Abdulkareem; Husien, Habib Flayyih (Jour Med Resh and Health Sci, 2021)
fibroepithelial polyp (skin tag) is a benign pedunculated and papillomatous mass involves intertriginous areas such as the neck, axilla.It measures 1-5 mm but giant fibroepithelial polyp measures > 10 cm.This report for a case of A 68 years old woman who presented with a slowly growing painless mass extending from the right nipple for 25 years.This lesion was was excised under local.The histopathological examination revealed a lining of stratified squamous epithelium with underlying subepithelial composed of loose collagenous tissue and fatty tissue with few dilated duct at sections from pedicle.No evidence of malignancy was found. It was concluded that the giant fibroepithelial polyp is rare and biopsy should be taken to the benign nature of the biopsy.